AB0829 Inhibition of Xanthine Oxidase by 1- [2'-Aminophenyl]-3-[3-(2-CHLORO-6-METHYLQUINOLYL)] Prop-2-Ene-1-One. (10th June 2014) - Ikram, H.; Imen, B.
Abstract : Background: Xanthine oxidase (XO) is a ubiquitous cytoplasmic protein that catalyzes the final two steps in purine catabolism. Inhibition of xanthine oxidase is a key element in the treatement of gout Objectives: In this work, we determine the binding affinity and the interaction mode of 1- [2'-aminophenyl]-3-[3-(2-chloro-6-methylquinolyl)] prop-2-ene-1-one to bind to the xanthine oxidase active site Methods: 1. Materials. Xanthine oxidase (XO, EC 1.2.3.2), xanthine (X) were purchased from Calbiochem and Sigma respectively. CHAL1 was synthesized by subjecting a series of anilides to vilsmeier reagent. The structure was confirmed by spectroscopic analysis (IR, RMN and MS). Spectrophotometer was used for spectrophotometric measurements. 2. Methods. 2.1. Docking Modeling: Ligand docking, protein-ligand interactions, and energy minimization of the complexes were performed using ArgusLab. The favorable binding orientations of the ligands were focused in the active site. The crystal structure of xanthine oxidase was retrieved from the Protein Data Bank with the corresponding entry code. 2.2. Drug-likeness analyses: To evaluate drug-likeness of CHAL1, we have verified if it possess properties that make it likely orally active drug. For this, we have used five rules formulated by Christopher A Lipinski. 2.3. Xanthine oxidase activity assay: The enzyme activity was evaluated spectrophotometrically by measuring uric acid formation at 295 nm, Δɛ295 =9.7 mM –1 cm –1 with xanthine as substrate. Results: Modeling docking was performed by selecting "ArgusDock" as the docking engine. A spacing of 0.4 Å between the grid points was used. 150 poses were analyzed; binding site box size was set to 18.08x18.48 x14.58 Å, to encompass all the active site. During docking simulations, the protein is considered as rigid. The binding modes of Allopurinol to the active site of xanthine oxidase indicated the same position and interaction as in the case of Salicylate, except for H-bond with GLU802.The superposition of CHAL1 with Salicylate revealed that the quinolyl ring is superimposed on Salicylate. Conclusions: Our investigation of CHAL1 and two known inhibitors, Allopurinol and salycilate, demonstrated the good binding affinity of CHAL1. The latter has formed more stable complex with xanthine oxidase than the two former ones. In the presence of xanthine as substrate, it was determined that CHAL1 inhibits the activity of XO by more than 70%. This result indicate that docking simulation assist significantly the drug discovery process and open possibility to use and develop the aromatic a, b-unsaturated carbonyl compounds for the therapeutic treatment of gout. CHAL1 respects the Lipinski's rule, making it a likely orally active drug. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5861